دور الرقابة التنظيمية في رفع مستوى الكفاءة المهنية دراسة ميدانية بمديرية الصيانة سونطراك الأغواط - نعامة إسماعيل; بن عثمان محمد ياسين; العيد رزق الله (جامعة عمار ثليجي الاغواط, 2022)
This study aims to know the role of organizational control in raising the level of effectiveness of the various activities of the Directorate of Maintenance and their effectiveness in improving the performance of workers to achieve the desired goals and measuring actual performance in an objective manner and discovering errors to take corrective measures during implementation and avoiding them in the future, and we relied on the descriptive approach because Describes the phenomenon in an accurate and detailed description, and the aim of this study is to try to reach the relationship between organizational control and the professional competence of the Sonatrach Maintenance Directorate - Laghouat - so that our research sample consisted of 44 individuals. It is divided into 3 axes, and by conducting a case study, we reached the following results: -The regulatory oversight has a role in improving production efficiency. -Monitoring through reports helps to monitor the work and makes it more organized. - Valuing the capabilities of workers and recognizing their efforts as evidence of the effectiveness of control.